Noncovalent Lone Pair⋅⋅⋅(No‐π!)‐Heteroarene Interactions: The Janus‐Faced Hydroxy Group1. Issue 28 (27th May 2015) - Pavlakos, Ilias; Arif, Tanzeel; Aliev, Abil E.; Motherwell, William B.; Tizzard, Graham J.; Coles, Simon J.
Abstract A comparative study using NMR spectroscopy and designed top‐pan molecular balances demonstrates that the noncovalent interaction of a hydroxy group with π‐deficient pyrazine and quinoxaline units involves a lone pair–heteroarene interaction which is much stronger and solvent independent when measured relative to the classical π‐facial hydrogen bond to a benzene ring. Alkyl fluorides also prefer the heteroarene rings over the benzene ring. The attractive interaction between a quinoxaline and a terminal alkyne is also stronger than the intramolecular hydrogen bond to an arene.